Reducing care time after implementing protocols for acute ischemic stroke: a systematic review - Karina Fonseca de Souza Leite; Samuel Ribeiro dos Santos; Rubia Laine de Paula Andrade; Mariana Gaspar Botelho Funari de Faria; Nanci Michele Saita; Ricardo Alexandre Arcêncio; Igor Simões da Silva Isaac; Carlos Eduardo Menezes de Rezende; Tereza Cristina Scatena Villa; Octavio Marques Pontes Neto; Aline Aparecida Monroe (Arquivos de Neuro-Psiquiatria)
Background The treatment of acute ischemic stroke with cerebral reperfusion therapy requires rapid care and recognition of symptoms. Objective To analyze the effectiveness of implementing protocols for acute ischemic stroke in reducing care time. Methods Systematic review, which was performed with primary studies in Portuguese, English, and Spanish published between 2011 and 2020. Inclusion criteria: study population should comprise people with acute ischemic stroke and studies should present results on the effectiveness of using urgent care protocols in reducing care time. The bibliographic search was conducted in June 2020 in the LILACS, MEDLINE, Embase, Scopus, CINAHL, Academic Search Premier, and SocINDEX databases. The articles were selected, and data were extracted by two independent reviewers; the synthesis of the results was performed narratively. The methodological quality of articles was evaluated through specific instruments proposed by the Joanna Briggs Institute. Results A total of 11,226 publications were found, of which 35 were included in the study. Only one study reported improvement in the symptoms-onset-to-door time after protocol implementation. The effectiveness of the therapeutic approach protocols for ischemic stroke was identified in improving door-to-image, image-to-needle, door-to-needle and symptoms-onset-to-needle times. The main limitation found in the articles concerned the lack of clarity in relation to the study population. Conclusions Several advances have been identified in in-hospital care with protocol implementation; however, it is necessary to improve the recognition time of stroke symptoms among those who have the first contact with the person affected by the stroke and among the professionals involved with the prehospital care.